836 Presentation, Clinical Outcomes and Prognosis of Primary Appendiceal Adenocarcinoma; Single Centre Experience. (4th May 2021) - Abounozha, S; Waqas, A; Kelly, S
Abstract: Background: Appendiceal adenocarcinoma is a rare condition. The aim of the study is to determine the pattern of clinical picture, histological diagnosis and prognosis of the disease on patients in our area. Method: A retrospective data analysis of patients who underwent appendicectomies from January 2011 to December 2019 in Northumbria NHS Trust. Records of patients with histologically diagnosed appendiceal adenocarcinoma were studied for their demographics, clinical features, laboratory, radiological results, operative notes and histological types. Results: 13 out of 3138 appendicectomies (0.41%: 6 Males, 7 Females with mean age of 69.84 years) were found to have primary appendiceal adenocarcinoma. Almost all the patients presented with clinical picture in keeping of acute appendicitis. 9 patients underwent emergency appendicectomies. 4 patients were treated conservatively. Appendiceal adenocarcinoma was diagnosed based on colonoscopy in 1 patient, CT scan in 1, post-appendicectomy histology in 9 patients, 2 post RHC histologies. Survival rate was 71.4% after 1 year, 64.3% after 2 years and 42.9% after 3 years. Overall median survival time for all TNM stages was 39.0 (95% CI, 15.72 to 62.27) months. Mean survival time was best in stage II 56.33 (95% CI, 48.86 to 63.80) months. Conclusions: Preoperative diagnosis is very difficult. Overall prognosis is poor.